KOMODIFIKASI PERKEMBANGAN KREATIVITAS SEBAGAI UPAYA STRATEGI BRANDING LEMBAGA SEKOLAH SENI ANAK - Moersid, Rambo (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2024)
This branding study focuses on the process of commodification at Ganara Art Studio, a non-formal art institution. The analysis is conducted at two levels. Firstly, at the commodification level, it explores how creative learning practices at Ganara Art Studio can be understood through Piaget's theory of child development. Secondly, at the branding level, the study examines the broader context, specifically how Ganara Art is positioned in social and commercial relations. By addressing these two levels, a comprehensive understanding of children's education at Ganara Art is obtained, encompassing not only its pedagogy but also how the pedagogy operates within a broader social context: encompassing South Jakarta, prestige, and urban parents. This research is undertaken as a branding strategy study, emphasizing how the brand highlights the holistic experience provided by Ganara Art to students aged 3-4 years and urban parents. This study is supported by the theory of Experiential Branding, focusing on sensory, emotional, cognitive, and relational aspects. The research was carried out using a descriptive qualitative approach, and data was collected through interviews with the main subject being the founder of Ganara.